Introduction - Balz, Verena (A+BE | Architecture and the Built Environment, 2019)
Since the 1980s, planning approaches in European regions shifted as a result of increasing attention to spatial patterns of interaction and movement on regional levels of scale, and alongside “a relative decline of the role of the state, a growing involvement of nongovernmental actors in a range of state functions, the emergence of new forms of multi-agency partnerships and more flexible forms of networking at various spatial scales” (Davoudi, 2008, p.63). Upcoming approaches, often called spatial planning, moved attention from the planning of predefined, contained territories to the planning of spatial networks, stretching across multiple and multi-scalar administrative boundaries. Planning that relied on generally applicable rationalities, statutory planning frameworks and authoritative planning power was challenged by planning that relied on an understanding of the specificities of regions, political consent on their desirable futures and the dedication of actors to these visions (Albrechts et al., 2003, Allmendinger and Haughton, 2010, Healey, 2006, Nadin, 2007, Needham, 1988, Schön, 2005). New approaches typically involved coalitions of plan actors from multiple tiers and levels of government as well as market and civil actors. Packaging their interests in shared visions became a way to operationalise planning. Collaboration in decision-making was used to simultaneously legitimise it. In an "institutional void" (Hajer, 2003, p.175) - in near absence of generally accepted and formally approved regional planning guidance - the inclusion of many in decision-making - good governance - became a normative goal of planning in itself (Innes and Booher, 2003, Mayntz, 2004). The Netherlands is no exception. As elsewhere in Europe, planning underwent a process of regionalisation in this country from the 1980s onward. Increasing attention to regional spatial development led to new planning agendas that emphasised the importance of places in larger, mostly economic, networks. A shift towards regionalisation coupled with deregulation, and an enhancement of development-led planning practices. Direct investment into strategic projects and area development became a dominant way of planning (Hajer and Zonneveld, 2000, Waterhout et al., 2013, Needham, 1988). Regionalisation liaised with tendencies of decentralisation, which resulted in a more equal distribution of planning power across national, provincial and municipal authorities (Haran, 2010, Salet, 2006, Salet and Woltjer, 2009, Teisman and Klijn, 2002). Regionalisation also coincided with the emergence of new decision-making approaches: “[P]lanners […] began to promote constructive ways into actively developing new perspectives for the future instead of merely relying on protective and prohibitive regulation – hence the emphasis on the word ‘development‘. Development planning refers […] to a more involved and anticipatory activity by collaborating public and private agencies, stimulating the likelihood of implementation, rather than public agencies setting limits by decree” (Salet and Woltjer, 2009, p.236). Among decision-making procedures that emerged in the context of spatial planning in the Netherlands was an array of practices commonly referred to as regional design. Practices that gained this label differed in their spatial scope and scale. They had a varying concern about issues such as: urbanisation, the development of transport, landscape and/or water systems at the city-regional, regional, national and transnational levels of scale. Some shared characteristics justify their common label though. Practices were all anticipatory indeed, concerned with the imagination of desirable spatial development. They all sought for comprehensiveness through considering a multitude of aspects that influence the form and functioning of this development. In all practices, the production of spatial representations, maps and models, was a core activity. Although differing in the composition of engaged parties, all practices knew the involvement of design professionals and a multi-actor setting. A significant shared characteristic was their strong relation with ongoing planning, expressed in their concern about large-scale public works, formal plans and policies, and in the frequent participation of governmental actors in practices. Practices also typically raised high and often varied expectations on their performances in this planning realm. Using design-led approaches in planning decision-making was not new in the Netherlands in the 1980s. On the contrary, such use can be traced back to the beginning of the 20th century, when urban planning emerged as a distinguished discipline. By then, the Dutch designer Cornelis van Eesteren became a prominent figure in a European-wide debate on where to take the new discipline in the future (Van Rossem, 2014). In the Netherlands, in collaboration with the more analyticallyminded Theodoor Karel van Lohuizen, he established design as a way to synthesise a deep understanding of spatial development with political aspirations, in the form of simple, and persuasive planning principles and to thus enhance the spatial quality of plans (Van Bergeijk, 2015, Van der Valk, 1990). However, expectations concerning the performances of design-led approaches accumulated from the 1980s onward. When regulatory land-use planning came to be seen as an approach that “stifles entrepreneurial initiative, [and] impedes innovation” (Klosterman, 1985, p.2) regional design came to be seen as an artistic, and creative practice that bears unexpected, inspiring and inventive results; a way to mobilise "thinking capacity" in the realm of planning (Ministeries van OCW et al., 1996, p.18). When decentralisation and regional governance became issues in Dutch planning, regional design became expected to perform not only in discussion on spatial matters, but in political and organisational realms too. When efficiency became a major aspiration of Dutch spatial planning, the use of regional design in planning decision-making gained an efficiency rationale as well. The national government argued that the practice “is crucial in accelerating (administrative) processes by curbing the complexity and uncertainty that characterises contemporary tasks” (Ministeries van I&M et al., 2012, p.9, my translation). It became expected to lead to a “better, faster, and therefore cheaper process” (idem). In parallel to these accumulating expectations (outlined in Table 1.1), the use of regional design in planning decision-making underwent a process of formalisation, in particular within the realm of Dutch national spatial planning. While the national government had first been involved in the practices incidentally from around 2000 and onward its engagement became more structural. The scope of policies aimed at stimulating architectural design practice through dedicated funding mechanisms was enlarged in the period, to include design with a concern about high levels of scale (Ministeries van OCW et al., 1996). During frequent reforms of these policies, fundable design practice became more and more thoroughly tied in with national spatial-planning agendas (Stegmeijer et al., 2012). In 2010, regional design became a mandatory moment in decision-making for large scale infrastructural projects (Enno Zuidema Stedebouw et al., 2011, Ministerie van I&M, 2010). Policy makers who promoted this formalisation assumed that interactive regional-design processes can, when employed at an early stage of implementation processes, explicate interdependencies among planning issues at different scales, facilitate discussions on these and in this way help to avoid conflict, delay and costs at later stages. In 2012, regional-design practice became associated with the set up top sector policy, a national policy aimed at an enhancement of internationally operating economic sectors (Ministeries van I&M et al., 2012). Representatives of the national government started to advertise the practice among an international audience of planners and entrepreneurs in urban development, during trade missions for instance. Under the header ‘a Dutch approach’, regional design came to be seen as a marketable export product.